1994
DOI: 10.1016/1010-7940(94)90020-5
|View full text |Cite
|
Sign up to set email alerts
|

Pericardectomy for chronic constrictive pericarditis: risks and outcome

Abstract: From 1970 to 1990, 71 consecutive patients (51 men and 20 women) had pericardectomy for chronic constrictive pericarditis. The mean age was 44.2 +/- 16.1 years. In the preoperative state 2.8% were in NYHA class I, 18.3% in II, 43.6% in III and 35.2% in IV. The operative approach was median sternotomy in 93% and left anterolateral thoracotomy in 7%. The early mortality rate (within 30 days after operation) was 5.6%. All four early deaths were female (P < 0.001), in the preoperative state the patients were class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 16 publications
2
35
0
1
Order By: Relevance
“…15 Four pathological stages of tuberculous pericarditis are recognized: (1) fibrinous exudation with initial polymorphonuclear leukocytosis, relatively abundant mycobacteria, and early granuloma formation with loose organization of macrophages and T cells; (2) serosanguineous effusion with a predominantly lymphocytic exudate with monocytes and foam cells; (3) absorption of effusion with organization of granulomatous caseation and pericardial thickening caused by fibrin, collagenosis, and ultimately, fibrosis; and (4) constrictive scarring: the fibrosing visceral and parietal pericardium contracts on the cardiac chambers and may become calcified, encasing the heart in a fibrocalcific skin that impedes diastolic filling and causes the classic syndrome of constrictive pericarditis. 16 Recent data suggest that the histological pattern is affected by the immune status of the patient, with fewer granulomas being observed in HIV-infected patients with severely depleted CD4 lymphocytes. 17 The lymphatic drainage of the pericardium is primarily to the anterior and posterior mediastinal and tracheobronchial lymph nodes and is reflected by the pattern of lymphadenopathy seen in tuberculous pericarditis.…”
Section: Pathogenesis Of Tuberculous Pericarditismentioning
confidence: 99%
“…15 Four pathological stages of tuberculous pericarditis are recognized: (1) fibrinous exudation with initial polymorphonuclear leukocytosis, relatively abundant mycobacteria, and early granuloma formation with loose organization of macrophages and T cells; (2) serosanguineous effusion with a predominantly lymphocytic exudate with monocytes and foam cells; (3) absorption of effusion with organization of granulomatous caseation and pericardial thickening caused by fibrin, collagenosis, and ultimately, fibrosis; and (4) constrictive scarring: the fibrosing visceral and parietal pericardium contracts on the cardiac chambers and may become calcified, encasing the heart in a fibrocalcific skin that impedes diastolic filling and causes the classic syndrome of constrictive pericarditis. 16 Recent data suggest that the histological pattern is affected by the immune status of the patient, with fewer granulomas being observed in HIV-infected patients with severely depleted CD4 lymphocytes. 17 The lymphatic drainage of the pericardium is primarily to the anterior and posterior mediastinal and tracheobronchial lymph nodes and is reflected by the pattern of lymphadenopathy seen in tuberculous pericarditis.…”
Section: Pathogenesis Of Tuberculous Pericarditismentioning
confidence: 99%
“…Current surgical mortality rates average 6% to 12% (56,57), but can be elevated further if there is coexisting myocardial damage, extensive pericardial calcification ('outer porcelain heart') or previous mediastinal radiation. Optimal timing for pericardiectomy is not known, although survival is lower among patients with more severe symptoms of heart failure at surgery (57,58).…”
Section: How Should I Treat It?mentioning
confidence: 99%
“…Large series have demonstrated the efficacy of pericardiectomy for constrictive pericarditis, 9 but early deaths occur from low-output syndrome regardless of surgical technique. 4 One recent study showed that patients with abnormal left ventricular contractility and relaxation properties assessed by preoperative cardiac catheterization had a higher mortality rate.…”
Section: Discussionmentioning
confidence: 99%